DIAGNOSE ENFORCEMENT AND TREATMENT OF HIGH BLOOD PRESSURE - Fitri, Dina Rianti (Majority, 2015)
Abstract Hypertension which is still a public health program. If it is not controlled, it will attack the target organs, and cause a heart attack, stroke, kidney, and also blindness. In indonesia, the hypertension’s problem tends to rise. The cause of the high blood pressure, covering the consumption of salt remain, age, gender, obesity, stress, and alcohol consumption. Hypertension diagnosis must be done on repeat measurements at least two times. Self control that can be done to reduce the number of hypertension is by doing a healhty lifestyle program. . Keywords: hypertension, diagnosis, governance Abstrak Hipertensi tetap merupakan masalah kesehatan masyarakat. Apabila tidak terkontrol, akan menyerang target organ, dan dapat menyebabkan serangan jantung, stroke, gangguan ginjal, serta kebutaan. Di Indonesia masalah hipertensi cenderung meningkat. Penyebab peningkatan tekanan darah tinggi, meliputi keturunan, konsumsi garam berlebih, usia dan jenis kelamin, obesitas, stres, konsumsi alkohol. Diagnosis hipertensi ditegakkan pada pengukuran berulang minimal dua kali. Pengendalian yang dapat dilakukan untuk menurunkan angka kejadian hipertensi adalah dengan melakukan program gaya hidup sehat. Kata kunci: hipertensi, diagnosis, tata laksana